Immunosuppressive Activity of Artemisia argyi Extract and Isolated Compounds - Zimmermann-Klemd, Amy M.; Reinhardt, Jakob K.; Morath, Anna; Schamel, Wolfgang W.; Steinberger, Peter; Leitner, Judith; Huber, Roman; Hamburger, Matthias; Gründemann, Carsten (Frontiers in Pharmacology, 2020)
The need for novel drugs for the treatment of autoimmune diseases is high, since available pharmaceuticals often have substantial side effects and limited efficacy. Natural products are a good starting point in the development of immunosuppressive leads. Since enhanced T cell proliferation is a common feature of autoimmune diseases, we investigated the T cell proliferation inhibitory potential of an extract library of plants used in traditional Chinese medicine. Using a newly established cell-based screening platform, an ethyl acetate extract of Artemisia argyi (Asteraceae, A. argyi) was found to suppress the proliferation of human primary T lymphocytes in vitro in an IL-2-dependent manner. Flow cytometry- and ELISA-based techniques further demonstrated that the A. argyi extract reduced the activation and function of T cells. Transcription factor analysis and flow cytometric calcium influx investigations indicated that the immunomodulatory effect was based on specific modification of T cell signaling in a non-cytotoxic manner which is mediated via the NFAT pathway and a non-sequestrant inhibition of the calcium influx. A series of guaianolide and seco-guaianolide sesquiterpene lactones, as well as a flavonoid, were identified in a previous study as the bioactive compounds in the A. argyi extract. The effects of these bioactive compounds were compared to those of the crude extract. The tested sesquiterpene lactones act via the transcription factor NFAT, thereby exhibiting their immunosuppressive potential, but have an overall effect on T cell biology on a more-downstream level than the crude A. argyi extract.